2015
DOI: 10.1590/1516-4446-2014-1446
|View full text |Cite
|
Sign up to set email alerts
|

Depression rather than liver impairment reduces quality of life in patients with hepatitis C

Abstract: Objective: Patients with chronic hepatitis C (CHC) have a poorer quality of life than those with other chronic liver diseases. However, some of the factors that determine health-related quality of life (HRQOL) in these patients, such as the degree of liver fibrosis, are still controversial. Therefore, the aim of the present study was to investigate the impact of CHC on HRQOL by conducting clinical, psychiatric, and sociodemographic evaluations. Methods: One hundred and twenty-four consecutive patients attendin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 37 publications
1
23
0
1
Order By: Relevance
“…The main finding of this study is that HCI patients judged their QoL to be significantly poorer than the general population standard 15 in seven of the eight domains of the SF-36, particularly general health and vitality (Table 1), in keeping with the suggestion that low QoL is related to the burden of non-specific symptoms of HCI such as fatigue. 17 Our finding is also in line with the results of earlier studies. [18][19][20] A similar study found even lower scores in the vitality, bodily pain, and physical role functioning domains.…”
Section: Discussionsupporting
confidence: 93%
“…The main finding of this study is that HCI patients judged their QoL to be significantly poorer than the general population standard 15 in seven of the eight domains of the SF-36, particularly general health and vitality (Table 1), in keeping with the suggestion that low QoL is related to the burden of non-specific symptoms of HCI such as fatigue. 17 Our finding is also in line with the results of earlier studies. [18][19][20] A similar study found even lower scores in the vitality, bodily pain, and physical role functioning domains.…”
Section: Discussionsupporting
confidence: 93%
“…12,13,14 This questionnaire includes a set of 14 questions seven each for anxiety and depression. 7,9 The HADS questionnaire takes only 2 to 5 minutes to be completed. 12 The diagnostic precision differs for depression and anxiety 13 but the sensitivity and specificity for both HADS-Anxiety and HADS-Depression were roughly 80% very comparable to the sensitivity and specificity achieved by the General Health Questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…4,5 A projected 170 million people are carrying hepatitis C virus worldwide. 6,7,8 In Pakistan, the frequency of Hepatitis B and C infection in general population is 2.5% and 4.8% correspondingly, representing a cumulative prevalence of 7.6%. 6 This is consistent with the constantly soaring burden of chronic liver disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(30) Depression is known to be more strongly associated with reduced QOL than to liver disease severity. (31) Patients with and without depression are known to respond differently to the same treatments for liver disease. (32,33) Our results are in line with these findings Fig.…”
Section: Depression Should Be Assessed and Managed During Cld Carementioning
confidence: 99%